Recent Advances in Corrosion Science (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
The dynamic development of global industry and growing demand for new material technologies generate constantly increasing problems regarding premature material degradation and the requirement to determine corrosion mechanisms and to develop new protection/evaluation approaches. Corrosion resistance depends on numerous determinants, such as material structure, chemistry, and complex environmental factors. It is highly challenging to obtain consensus between high corrosion resistance and an economic approach. On the other hand, inadequate levels of corrosion control create serious hazards to life and the environment. This Special Issue, “Recent Advances in Corrosion Science”, brings together fourteen articles and one review, providing a snapshot of the recent activity and development in this field. The book contains studies related to the development of new corrosion-resistant alloys and the determination of microstructure-dependent properties; it also provides an insight into recent approaches towards anticorrosion technologies, such as corrosion inhibitors and composite and metal protective coatings.